Cancer-associated fibroblast-mediated immune evasion: molecular mechanisms of stromal-immune crosstalk in the tumor microenvironment - Luo, Junling; Xiang, Xuehua; Gong, Guangyuan; Jiang, Lang (Frontiers in Immunology, 2025)
The tumor microenvironment (TME) is a complex ecosystem and cancer-associated fibroblasts (CAFs) are critical drivers of the immunosuppressive TME. The dynamic interactions between CAFs and immune cells play a crucial role in tumor progression and immune evasion. This review systematically investigates the interactions between CAFs and different immune cells and elaborates on the molecular mechanisms of CAF-mediated immune suppression, with a focus on their multifaceted interactions with various immune cell populations. The present study discusses how CAFs utilize cytokine networks, metabolic reprogramming and immune checkpoint regulation to establish an immunosuppressive TME. Clinical translation should prioritize FAP-directed therapies alongside αPD-1 to concurrently target CAF-immune crosstalk and metabolic competition in the TME.